DRM, a Design Research Methodology - Blessing, Lucienne T.M; Chakrabarti, Amaresh (Springer London : Imprint: Springer, 2009)
Design research is a fast-growing field of inquiry with significant importance in terms of helping society to create products and processes of improved quality and for enhancing the environment in which we live. The step-wise, hands-on approach of DRM studies the ways in which design research can best be undertaken to address specific questions. This study gives rise, for the first time, to a generic and systematic design research methodology intended to improve the quality of design research - its academic credibility, industrial significance and societal contribution - by enabling more thorough, efficient and effective procedures. Professors Blessing and Chakrabarti provide a comprehensive list of types of design research linked to appropriate research methods - familiar as well as new - and supported by illustrative examples throughout the text. Furthermore, the book points the way to more detailed sources of various established research methods that can be applied. The practical emphasis of the text is reinforced by a whole section of design research project examples contributed by eminent design researchers and placed in the context of the proposed methodology to demonstrate the application of the variety of approaches available in a structured fashion. DRM, a Design Research Methodology, speaks to a broad readership: it will provide the graduate student with an excellent grounding in good design research practice, inculcating good habits of research for the future and showing how the process of understanding and improving design can become more effective and efficient; it will interest the academic and industrial researcher as a source of useful and well-ordered methods within a common design research ethos, as well as a methodological framework for research projects and programmes; it will attract the supervisors of young researchers by offering research methods and a well-thought-out and logically structured research process for use in courses on design research.